Development of New Material Testing Apparatus in Hydrogen at Elevated Temperature. (2015) - Liu, X.L.; Chen, X.D.; Wang, B.; Fan, Z.C.; Zhuang, Q.W.
Abstract: The research situation of material testing apparatus in hydrogen is reviewed. Lots of research on the materials testing apparatus in high pressure hydrogen at ambient temperature was reported. However, few detail the apparatus for material testing in hydrogen at high temperature, especially for dynamic testing. A new apparatus for material testing in hydrogen at the elevated temperature (300∼600°C) has been developed. The apparatus consists of a pressure vessel and a control system which can be divided into three subsystem: temperature control system, hydrogen pressure control system and coolant system. A heating furnace composed of lower and upper resistance wires for temperature uniformity of the specimen was installed in the pressure vessel. The temperature was measured by upper and lower thermocouples attached to the specimen. Gas pressure in the vessel was controlled by inlet and outlet solenoid valve. An external loading system was employed for loading on the specimen. The elongation of specimen was measured by grating scale. The outside wall of the vessel was cooled by circulating water to protect against thermal degradation of seal ring.